2020
DOI: 10.1080/13803395.2020.1817338
|View full text |Cite|
|
Sign up to set email alerts
|

Insight into memory and functional abilities in individuals with amnestic mild cognitive impairment

Abstract: Objective: Accurate insight into one's abilities facilitates engagement in rehabilitation and implementation of compensatory strategies. In this study, self-awareness, self-monitoring, and a new self-updating construct of insight were examined in amnestic mild cognitive impairment (aMCI).Method: Individuals with aMCI and healthy older adults (HOAs) completed a list-learning task in a laboratory setting, and a naturalistic task of everyday functioning in a campus apartment along with other standardized neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Out of a total of 20,136 studies, 20,088 were removed according to the exclusion criteria and, additionally, if they (a) assessed visuomotor abilities in patients with MCI in Parkinson's Disease (MCI-PD) because of the major motor impairment or (b) provided information about upper extremity functioning by self-report measures. The final set, therefore, consisted of 48 studies assessing the following issues: 16 studies assessed VSWM abilities [17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 12 studies assessed anosognosia for memory deficits [40][41][42][43][44][45][46][47][48][49][50][51], 14 studies assessed visuomotor abilities [52][53][54][55][56][57][58][59][60][61][62][63][64][65], 2 studies investigated the relationship between VSWM and conversion [37,66], and 4 studies investigated the relationship between anosognosia for memory deficit...…”
Section: Data Extraction Results and Synthesismentioning
confidence: 99%
“…Out of a total of 20,136 studies, 20,088 were removed according to the exclusion criteria and, additionally, if they (a) assessed visuomotor abilities in patients with MCI in Parkinson's Disease (MCI-PD) because of the major motor impairment or (b) provided information about upper extremity functioning by self-report measures. The final set, therefore, consisted of 48 studies assessing the following issues: 16 studies assessed VSWM abilities [17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 12 studies assessed anosognosia for memory deficits [40][41][42][43][44][45][46][47][48][49][50][51], 14 studies assessed visuomotor abilities [52][53][54][55][56][57][58][59][60][61][62][63][64][65], 2 studies investigated the relationship between VSWM and conversion [37,66], and 4 studies investigated the relationship between anosognosia for memory deficit...…”
Section: Data Extraction Results and Synthesismentioning
confidence: 99%
“…How very early stage symptomatic neurodegeneration impacts on metacognition is debatable. Conflicting evidence is seen across different studies, with some finding people with amnestic MCI to have intact metacognition [22], and others identifying significant deficits [23]. Vannini et al identified correlations between metacognition and FDG-PET activity in the posterior cingulate and hippocampal cortices in people with amnestic MCI, coupled with reduced functional connectivity between the posterior cingulum, orbitofrontal cortex, and the inferior parietal lobes [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our study serves to complement the existing literature by expanding the understanding of awareness of task performance in older adults using an instrument that more closely approximates real-life situations. Understanding adults' perceptions of performance immediately after a task is also important as it is this assessment that can update metacognitive knowledge and influence future performance (Toglia and Kirk, 2000;Ng et al, 2018;Chudoba and Schmitter-Edgecombe, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It may include frequency counts of spontaneous error correction and examination of discrepancies between self-appraisal and actual performance (O'Keeffe et al, 2007). The performance discrepancy method is commonly used within memory list learning tasks (Chudoba and Schmitter-Edgecombe, 2020) and within the context of functional activities as it examines a person's awareness or perceptions of specific abilities in close proximity to a related task (Goverover et al, 2014;Rotenberg-Shpigelman et al, 2014;Chen and Toglia, 2019;Chudoba and Schmitter-Edgecombe, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation